Boron Neutron Capture Therapy for High-Grade Skull-Base Meningioma - Takeuchi, Koji; Kawabata, Shinji; Hiramatsu, Ryo; Matsushita, Yoko; Tanaka, Hiroki; Sakurai, Yoshinori; Suzuki, Minoru; Ono, Koji; Miyatake, Shin-Ichi; Kuroiwa, Toshihiko (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives Boron neutron capture therapy (BNCT) is a nuclear reaction-based tumor cell-selective particle irradiation that occurs when nonradioactive Boron-10 is irradiated with low-energy neutrons to produce high-energy α particles (10B [n, α] 7Li). Possible complications associated with extended surgical resection render high-grade meningioma (HGM) a challenging pathology and skull-base meningiomas (SBMs) even more challenging. Lately, we have been trying to control HGMs using BNCT. This study aims to elucidate whether the recurrence and outcome of HGMs and SBMs differ based on their location.Design Retrospective review.Setting Osaka Medical College Hospital and Kyoto University Research Reactor Institute.Participants Between 2005 and 2014, 31 patients with recurrent HGM (7 SBMs) were treated with BNCT.Main Outcome Measures Overall survival and the subgroup analysis by the anatomical tumor location.Results Positron emission tomography revealed that HGMs exhibited 3.8 times higher boron accumulation than the normal brain. Although tumors displayed transient increases in size in several cases, all lesions were found to decrease during observation. Furthermore, the median survival time of patients with SBMs post-BNCT and after being diagnosed as high-grade were 24.6 and 67.5 months, respectively (vs non-SBMs: 40.4 and 47.5 months).Conclusions BNCT could be a robust and beneficial therapeutic modality for patients with high-grade SBMs.
Keywords: boron neutron capture therapy; high-grade meningioma; skull base meningioma; recurrent; boronophenylalanine